ECO DESIGN AND THE RELEVANCE OF WASTE-FREE FASHION TODAY - K. R. Fuzailova (Journals Park Publishing, 2022)
The development of sustainable textile innovation in the field of costume design is accelerating. Market-new materials feature greater performance qualities and are more environmentally friendly than alternatives already available. Nowadays, it is obvious that most of the clothing at a store will be made of cotton, polyester, or a combination of the two. However, linen and wool are typically only available in more expensive stores, and there are currently just a handful of textiles that may be used to make costumes from. The significance of today's waste-free fashion is kept in mind as well as comments and reflections on environmental design.
Keywords: eco design, fashion, waste-free fashion, fabric, industrial, textile